Early atherosclerosis and conduction defect in a rare case of dunnigan type familial partial lipodystrophy - Olgun, Fatih Erkam; Güler, Ekrem; Çeleğen, Muhammed Furkan; Demirçelik, Bora; Kılıçaslan, Fethi; Boztosun, Bilal (Turkish Society of Cardiology, 2024)
A 45-year-old female patient was admitted to the emergency department with syncope. Her medical history revealed a diagnosis of Familial Partial Lipodystrophy 2 (FPLD2). The patient's electrocardiogram showed a complete atrioventricular (A-V) block, and she had a history of insulin-dependent diabetes mellitus and coronary artery bypass surgery. A severe stenosis was observed in the aortic right coronary artery saphenous vein graft during coronary angiography, which was successfully revascularized. Subsequently, due to persistant syncope attacks, a permanent pacemaker was implanted after an electrophysiological study. This case highlights that serious cardiac conduction defects in patients with FPLD2 may not only be related to coronary artery disease but can also present as direct conduction defects.

Senkop şikayeti ile acil servise başvuran 45 yaşında kadın hastanın öyküsünden ailesel parsiyel lipodistrofi 2 (FPLD2) tanısı aldığı öğrenildi. İnsüline bağımlı diabetes mellitus ve koroner by-pass cerrahisi öyküsü olan hastanın elektrokardiyografisinde A-V tam blok izlendi. Koroner anjiyografide aort-sağ koroner arter safen ven greftinde ciddi darlık görülmesi nedeniyle başarılı revaskülarizasyon uygulandı. Sonrasında, senkop atakları devam eden hastaya yapılan elektrofizyolojik çalışma sonucunda kalıcı kalp pili takıldı. Bu olguda, FPLD2 tanısı olan hastalarda ciddi kardiyak iletim kusurlarının sadece koroner arter hastalığı ile ilişkili olmadığını, hastalığın doğrudan iletim kusurları ile de ortaya çıkabileceğini vurgulamak istedik.
Nadir bir dunnigan tipi ailevi kısmi lipodistrofi olgusunda erken ateroskleroz ve ileti bozukluğu
Keywords: Conduction Defect; Early Atherosclerosis; Familial Partial Lipodystrophy; İleti Defekti; Erken Ateroskleroz; Familyal Parsiyel Lipodistrofi